Interactive Digital Catalog for Canopy Workshop Using Augmented Reality - Rohman Dijaya; Rizky Bayu Wardana; Suprianto Suprianto (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2021)
This research study develops a product promotion method for a canopy roofs. The development of this method is to apply a 3-dimensional (3D) catalog using Augmented Reality (AR) technology. By utilizing Augmented Reality technology, sellers do not need to create markets or miniature products that are commonly used to provide examples to consumers to save costs, attract consumer interest, and display objects that appear natural. Based on the tests that have been done, it is concluded that implementing Augmented Reality in the canopy sales promotion media using the Luther development method with the stages of analysis, design, implementation, testing, and maintenance. Implementation of Augmented Reality in canopy sales promotion media uses concept data from the types of canopies included in the Augmented Reality-based application, namely stainless and hollow types made using a 3D blender program. A marker as a sign to bring up 3D objects in the application. Markers are created using Photoshop and entered the database so that they can be stored online. System testing uses the BlackBox testing method where the program's functionality is running as desired.